THE EFFECTIVENESS OF HEALTH EDUCATION ON KNOWLEDGE ABOUT BREAST SELF EXAMINATION AS AN EARLY DETECTION OF BREAST CANCER IN WOMEN IN BENGKULU CITY - Berlian Kando Sianipar; Santhna Letchmi Panduragan; Murwati Murwati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Breast cancer is one of the causes of death in women. To reduce the death rate in breast cancer sufferers, early detection is necessary, which can be done through Breast Self Examination. Where BSE is the easiest way to do it, but there are still many women who don't know how to do BSE properly. The purpose of this study is to find out how health education affects women's knowledge of BSE as a means of early breast cancer screening in Bengkulu City. This research method uses pre-experimental with one group pre-post test design. The population in this study were women aged 26-35 years with a total sample of 86 people using purposive sampling technique. The results of the T Test statistical test p value = 0.000, this shows that there is an influence of Health Education on women's level of knowledge about BSE. Health education can increase knowledge, so nurses need to carry out health education about BSE in early detection of breast cancer.